Edukasi Geowisata dan Konservasi Geologi Bagi Pengelola Pusat Informasi Geologi Geopark Ijen (PIGGI) Banyuwangi - Chistella , Chalia; Aprianto, Bejo; Noviantoro, Kurnia Maulidi (PADAIDI: Journal of Tourism Dedication, 2025)
This community service activity was carried out at PIGGI (Ijen Geopark Geology Information Center), Banyuwangi Regency, as part of the implementation of the Tri Dharma of Higher Education in the field of community service. The activity aims to enhance the capacity of managers and students in understanding and applying the concepts of geotourism and geological conservation as an effort to support the sustainable management of the geopark area. The background of the activity stems from the partner's need to strengthen the educational and interpretative aspects in delivering geological information to the public, as well as to expand academic networks with universities. The implementation method uses a participatory education approach, involving lecturers and students as facilitators in socialization activities, interactive discussions, group reflections, and simulations of delivering geotourism information to visitors. The activities were carried out over two days and included the delivery of thematic material on social geography, tourism geography, and geology, linked to the geosite potential in the Ijen area. The results of the activities showed an increase in participants' understanding and awareness of the importance of geological heritage preservation, strengthened geotourism interpretation skills, and the establishment of closer academic collaboration between the Geography Education Study Program of FKIP Universitas Jember and the Ijen Geopark management. This activity also directly contributes to achieving the Higher Education Key Performance Indicators (KPI), particularly in terms of student learning experiences outside the campus and faculty collaboration with community partners. Keywords: community service, geotourism, geological conservation, PIGGI, Ijen Geopark Abstrak Kegiatan pengabdian kepada masyarakat ini dilaksanakan di PIGGI (Pusat Informasi Geologi Geopark Ijen), Kabupaten Banyuwangi, sebagai bagian dari implementasi Tri Dharma Perguruan Tinggi pada bidang pengabdian. Kegiatan ini bertujuan untuk meningkatkan kapasitas pengelola dan mahasiswa dalam memahami serta menerapkan konsep geowisata dan konservasi geologi sebagai upaya mendukung pengelolaan kawasan geopark yang berkelanjutan. Latar belakang kegiatan berangkat dari kebutuhan mitra untuk memperkuat aspek edukatif dan interpretatif dalam penyampaian informasi geologi kepada masyarakat serta memperluas jejaring akademik dengan perguruan tinggi. Metode pelaksanaan menggunakan pendekatan edukasi partisipatif, yang melibatkan dosen dan mahasiswa sebagai fasilitator dalam kegiatan sosialisasi, diskusi interaktif, refleksi kelompok, serta simulasi penyampaian informasi geowisata kepada pengunjung. Pelaksanaan kegiatan dilakukan selama dua hari dan mencakup penyampaian materi tematik tentang geografi sosial, geografi pariwisata, dan geologi yang dikaitkan dengan potensi geosite di kawasan Ijen. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan kesadaran peserta terhadap pentingnya pelestarian warisan geologi, penguatan kemampuan interpretasi geowisata, serta terjalinnya kerja sama akademik yang lebih erat antara Program Studi Pendidikan Geografi FKIP Universitas Jember dan pengelola Geopark Ijen. Kegiatan ini juga berkontribusi langsung terhadap pencapaian Indikator Kinerja Utama (IKU) Perguruan Tinggi, khususnya dalam aspek pengalaman belajar mahasiswa di luar kampus dan kolaborasi dosen dengan mitra masyarakat.